2000
DOI: 10.1007/s004420051031
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of diversity and composition of Mediterranean ground ant communities tracking spatial and temporal variability in the thermal environment

Abstract: The present study analyzed ant community structure and the factors affecting it in the Spanish Mediterranean area. The aim of this study was to test whether temperature controls the composition and diversity of the ground ant fauna and the spatial and temporal distribution of dominance groups along adjacent communities. The main descriptors of community structure (except perharps species richness) were found to vary along the gradient of vegetation cover: increased vegetation cover resulted in an increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
184
3
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(200 citation statements)
references
References 32 publications
11
184
3
2
Order By: Relevance
“…The general assumption is that species diversity is positively associated with vegetation complexity (Bonte et al 2002;Tews et al 2004;Sarty et al 2006). However, the local environment, habitat type, plant composition, disturbance, as well as ant behavior and life history make the outcomes highly variable (Bestelmeyer and Schooley 1999;Kotze and Samways 1999;Retana and Cerdá 2000;French and Major 2001;Lassau and Hochuli 2004). In addition, most previous research has been conducted in environments strongly associated with anthropogenic disturbances such as fire and grazing, and less attention has been paid to more natural habitats (Ruiz-Jaen and Aide 2005; Jiménes-Valverde and Lobo 2007; Gibb and Parr 2010).…”
Section: Ant Community and Vegetation Structurementioning
confidence: 99%
“…The general assumption is that species diversity is positively associated with vegetation complexity (Bonte et al 2002;Tews et al 2004;Sarty et al 2006). However, the local environment, habitat type, plant composition, disturbance, as well as ant behavior and life history make the outcomes highly variable (Bestelmeyer and Schooley 1999;Kotze and Samways 1999;Retana and Cerdá 2000;French and Major 2001;Lassau and Hochuli 2004). In addition, most previous research has been conducted in environments strongly associated with anthropogenic disturbances such as fire and grazing, and less attention has been paid to more natural habitats (Ruiz-Jaen and Aide 2005; Jiménes-Valverde and Lobo 2007; Gibb and Parr 2010).…”
Section: Ant Community and Vegetation Structurementioning
confidence: 99%
“…Many studies, which have investigated niche partitioning in ant communities, revealed that competition can result: (1) in direct antagonistic behaviour (Savolainen and Vepsäläinen 1988;Yamaguchi 1992;Retana and Cerdµ 1995;Punttila et al 1996;, (2) in temporal segregation (Baroni Urbani and Aktaç 1981;Marsh 1988;Fellers 1989;Deffernez et al 1990;Cros et al 1997;de Biseau et al 1997;Retana and Cerdµ 2000;Albrecht and Gotelli 2001;Campos and Schoereder 2001), (3) in spatial segregation by microhabitat differentiation (Punttila et al 1996, Johnson 2000, or (4) in different foraging strategies (Traniello 1983(Traniello , 1987Jones and Sherman 1990;Perfecto 1994;de Biseau et al 1997;Sanders and Gordon 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The ant diversity within individual HFs might have been influenced by the surrounding landscape areas. Ant populations often are affected by vegetation structure, with a decrease in vegetation diversity causing a reduction in ant diversity because vegetation plays a major role in regulating the microclimatic conditions that affect ant activity (Perfecto & Snelling 1995, Perfecto & Vandermeer 1996, Retana & Cerdá 2000, Vasconcelos et al 2008.…”
Section: Resultsmentioning
confidence: 99%